Audit Quality Based on Internal Audit Capability Model (IACM) and Gender as Mediating Variabel in the Public Sector - Rida Perwita Sari; Sri Hastuti; Oryza Tannar (Journal of Economics, Business, and Government Challenges, 2019)
The purpose of this study is to examine the influence of competence, Independence, Pressure of Obedience and internal control system to Audit Quality based on Internal Audit Capability Model (IACM) and gender as mediating variable. This research contributes the theoretical and practical benefits as the form of adoption of agency theory and attribution theory and suggestions to improve the expertise of auditors by taking into account the competence, independence, and pressure of obedience and internal control system to produce quality inspection in the field of supervision. This study uses a quantitative approach. The analysis technique used in this research is Partial Least Square (PLS) with the help of warpPLS software. The subject of this study is the Inspectorate of East Java Province with a sample of auditors in the Inspectorate of East Java Province which amounted to 53 auditors. The results of this study indicate that competence and internal control system affects the Audit Quality based on Internal Audit Capability Model (IACM), while the independence, pressure of obedience and gender do not affect the Audit Quality based on Internal Audit Capability Model (IACM).